LIVING HERITAGE: CONTINUITY AND INNOVATION IN LOCAL RELIGIOUS TRADITIONS - I Ketut Gunarta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Local religious traditions represent a form of living heritage in which ritual, belief, and communal memory interact to shape cultural identity across generations. Despite the pressures of globalization, technological advancement, and shifting social dynamics, many local traditions continue to thrive through flexible adaptation and creative reinterpretation. This study explores the continuity and innovation embedded within local religious practices, with particular attention to how communities negotiate sacred authority, cultural authenticity, and contemporary relevance. Through a qualitative approach that integrates ethnographic observation, textual interpretation, and interviews with ritual practitioners, this research demonstrates that local traditions are neither static nor threatened, but dynamically sustained through community participation and situational transformation. The findings reveal that innovation does not diminish sacred values; rather, it revitalizes ritual meaning and strengthens collective identity. As living heritage, local religious traditions provide a resilient framework for spiritual expression, cultural cohesion, and intergenerational knowledge transmission in the modern era.